2016
DOI: 10.1038/srep28030
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Breast Reconstruction via Additive Biomanufacturing

Abstract: Adipose tissue engineering offers a promising alternative to current breast reconstruction options. However, the conventional approach of using a scaffold in combination with adipose-derived precursor cells poses several problems in terms of scalability and hence clinical feasibility. Following the body-as-a-bioreactor approach, this study proposes a unique concept of delayed fat injection into an additive biomanufactured and custom-made scaffold. Three study groups were evaluated: Empty scaffold, Scaffold con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 58 publications
(74 reference statements)
1
84
0
Order By: Relevance
“…In an earlier study, we showed a safe and easy use of tissue engineering-derived surgical implants in maxillofacial surgery [6, 7]. This technology is based on computer-assisted design/computer-assisted manufacturing (CAD/CAM) and polycaprolactone (PCL) implants for the regeneration of bone [812] and other tissues [13, 14]. PCL is a biocompatible material and PCL-based implants biodegrade within 2 years and promote autologous bone formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we showed a safe and easy use of tissue engineering-derived surgical implants in maxillofacial surgery [6, 7]. This technology is based on computer-assisted design/computer-assisted manufacturing (CAD/CAM) and polycaprolactone (PCL) implants for the regeneration of bone [812] and other tissues [13, 14]. PCL is a biocompatible material and PCL-based implants biodegrade within 2 years and promote autologous bone formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, size and shape of the tissues to be regenerated may require personalization to best fit the anatomy of each individual and therefore TECs may need to be customized. In fact, 3D printing medical scaffolds were tailored for breast reconstruction using medical imaging techniques demonstrating the potential interest in the medical field 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In drug-treated group, vessel section tended to be long and narrow, which contrasted with the round shaped vessel section observed in the control group. Histological section has already been used to primitively analysis the vessel shape and orientation 32,33 . In order to quantitatively describe the vessel orientation from histological observation, we introduced a novel statistical magnitude, vessel shape index (VSI), which was calculated by dividing the width of the vessel section by its length.…”
Section: Discussionmentioning
confidence: 99%